Neural drive to human genioglossus in obstructive sleep apnoea - Saboisky, Julian P (Blackwell Publishing Ltd, 2007)
One postulated mechanism for obstructive sleep apnoea (OSA) is insufficient drive to the upper-airway musculature during sleep, with increased (compensatory) drive during wakefulness. This generates more electromyographic activity in upper airway muscles including genioglossus. To understand drives to upper airway muscles, we recorded single motor unit activity from genioglossus in male groups of control (n = 7, 7 ± 2 events h(−1)) and severe OSA (n = 9, 54 ± 4 events h(−1)) subjects. One hundred and seventy-eight genioglossus units were recorded using monopolar electrodes. Subjects were awake, supine and breathing through a nasal mask. The distribution of the six types of motor unit activity in genioglossus (Inspiratory Phasic, Inspiratory Tonic, Expiratory Phasic, Expiratory Tonic, Tonic and Tonic Other) was identical in both groups. Single unit action potentials in OSA were larger in area (by 34%, P < 0.05) and longer in duration (by 23%, P < 0.05). Inspiratory units were recruited earlier in OSA than control subjects. In control subjects, Inspiratory Tonic units peaked earlier than Inspiratory Phasic units, while in OSA subjects, Inspiratory Tonic and Phasic units peaked simultaneously. Onset frequencies did not differ between groups, but the peak discharge frequency for Inspiratory Phasic units was higher in OSA (22 ± 1 Hz) than control subjects (19 ± 1 Hz, P = 0.003), but conversely, the peak discharge frequency of Inspiratory Tonic units was higher in control subjects (28 ± 1 Hz versus 25 ± 1 Hz, P < 0.05). Increased motor unit action potential area indicates that neurogenic changes have occurred in OSA. In addition, the differences in the timing and firing frequency of the inspiratory classes of genioglossus motor units indicate that the output of the hypoglossal nucleus may have changed.